Effects of Chinese consumers' relationship benefits and satisfaction on attitudes toward foreign fashion brands:The moderating role of country of salesperson. (January 2016) - Choi, Yu Hua; Choo, Ho Jung
Abstract: The paper examines the various responses of consumers depending on the country of salesperson (COS) and to look into the effects that consumer–salesperson relationship benefits have on consumer satisfaction and brand attitude. The results suggest that consumers' perceived social benefit and functional benefit positively influenced their satisfaction with salesperson, and a significant positive effect of consumers' satisfaction with salesperson on consumers' brand attitude is found. This positive relationship was moderated by COS. These findings suggest that COS will serve as an important retail mix for global marketers. Other results and management implications are also discussed. Highlights: This research examines the effect of country of salesperson (COS) in foreign brand store on Chinese consumer. Relationship benefits impact positively on satisfaction with the salesperson and brand attitude. Satisfaction with the salesperson supports full mediation between relationship benefits and brand attitude. COS moderates the relationship among relationship benefits, satisfaction, and brand attitude.